2018
DOI: 10.3390/f9030108
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Trends and Drought Events on the Growth of Oaks (Quercus robur L. and Quercus petraea (Matt.) Liebl.) within and beyond Their Natural Range

Abstract: Due to predicted climate change, it is important to know to what extent trees and forests will be impacted by chronic and episodic drought stress. As oaks play an important role in European forestry, this study focuses on the growth response of sessile oak (Quercus petraea (Matt.) Liebl.) and pedunculate oak (Quercus robur (L.)) under contrasting climatic conditions. Analyses cover both site conditions of their natural occurrence (Southern Germany and Northeast Italy) and site conditions beyond their natural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 61 publications
1
22
1
Order By: Relevance
“…The impact of drought climate events is mostly widespread, because drought is a natural and recurring feature of climate and occurs in almost all climatic regimes [1,2]. In order to evaluate the precipitation data (3B43) with 22 meteorological stations in Singapore from 1998 to 2014 and showed that the TRMM precipitation products performed well in accuracy [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of drought climate events is mostly widespread, because drought is a natural and recurring feature of climate and occurs in almost all climatic regimes [1,2]. In order to evaluate the precipitation data (3B43) with 22 meteorological stations in Singapore from 1998 to 2014 and showed that the TRMM precipitation products performed well in accuracy [21].…”
Section: Introductionmentioning
confidence: 99%
“…To validate the reliability of satellite-derived TRMM precipitation data and to explore the hydrological characteristics in the Loess Plateau since the Grain-for-Green Project was implemented, this study evaluated regional drought conditions using the TRMM precipitation data between 1998 and 2014. The main objectives of this paper can be summarized as follows: (1) to validate the TRMM precipitation data (1998-2014) and evaluate its applicability in the Loess Plateau based on the observed weather data from 50 stations in the study area; (2) to analyze the temporal and spatial variability of the precipitation from 1998 to 2014 and test the changing trend based on M-K test method and (3) to analyze the temporal and spatial variation process of the drought condition using SPI index before and after the implementation of the Grain-for-Green Project. Based on the above findings, we will also study the occurrence rate of dry and wet events and analyze the vegetation recovery potential in the Loess Plateau, which may be an important reference for ecological restoration and vegetation recovery in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Considering broad-leaves species and the oaks group our outcome is partially in agreement with the existing knowledge. A negative variation in habitat suitability was also predicted Perkins et al (2018) while a negative decrease in habitat suitability can be read in Kim et al (2017) for cork oak in the Mediterranean area. Finally, a decrease in habitat suitability during future period was predicted for holm and turkey oak by Vitale et al (2012) in the same environment we studied.…”
Section: Sdm As a Tool For Forest Management Options In The Italian Fmentioning
confidence: 92%
“…Both oak species belong to the anisohydric species, being able to sustain photosynthesis under moderate drought mainly by regulating stomatal conductance [9,16]. Under more severe drought, a decrease in the net-assimilation was found to be mainly due to stomatal closure rather than a decrease in photosynthetic capacity [17], and it was suggested that this capacity leads to the observed delay of drought-induced effects in these oak species [18]. Apart from the affected growth traits, oaks may react on drought periods by altering the timing of several seasonal life cycle events.…”
Section: Introductionmentioning
confidence: 99%